School Management and its Effectiveness in Lower Secondary Education in Uganda: Examining Perceptions of the Practitioners - Wokadala, James (Advances in Social Sciences Research Journal, 2016)
This paper evaluates effectiveness of lower secondary schools in Uganda with specific focus on how school leadership and management practices impact on students’ achievement. The study used both quantitative and qualitative approaches considering teachers and students as units of analyses. Results indicate that school success is associated with effective instructional leadership, teacher involvement in decision making and policy implementation, teaching and learning in safe as well as orderly school environment, regular and objective monitoring of student achievement, improved relations between teachers and parents. Effective Instructional leadership in efficient schools culminated into positive behavior reinforcement and recognition to students showing exceptional accomplishments and appropriate behavior approaches compared to opportunism that engulfed low achieving schools with less regard to moral principles. Moreover, teachers are often disappointed over little influence to effect decisions even in matters where their interests are involved. In either of the schools, it is pertinent that promoting academic excellence and fostering students’ learning and progress remains crucial tests of effective schooling.